Radiation exposure to allied health personnel handling blood specimens from patients receiving radioactive iodine-131 and recombinant human TSH (thyrogen®) stimulation. (9th November 2021) - Sarah, Tai Beishan; Peiling, Yang; Loo, Tiew Puay; Ming, Wong Yen; Yien, Ling Sing; Soon, Tay Young; Loke, Kelvin S H
Abstract: With increasing use of recombinant human TSH (rhTSH) stimulation protocol in radioactive iodine-131 treatment of thyroidectomised differentiated thyroid carcinoma (DTC), there is increasing concern regarding radiation safety during collection and processing of radioactive blood samples. Our study aims to quantify this radiation exposure in the context of current radiation guidelines to provide a practical safety framework. We analysed 45 patients prospectively referred to a tertiary centre in Singapore, who had histologically proven DTC, and who were thyroidectomised and planned for I-131 with rhTSH stimulation. Each patient received rhTSH for two consecutive days, with I-131 administered 24 h after, and a stimulated Thyroglobulin blood sample collected and processed 72 h after the last rhTSH dose. We measured radiation exposures with dosimeters. Based on the average and maximum exposure rates calculated, we extrapolated and derived the number of radioactive blood samples that could be safely collected and processed. Mean hand and body radiation exposures during venepuncture and blood processing were generally significantly higher than background radiation. Based on average exposure rates, the permissible number of blood samples that can be collected and processed is 9.09 × 10 3 per year (24 per day) and 8.70 × 10 4 per year (238 per day), respectively. This is the first study to date to extrapolate permissible thresholds that can serve as a practical guideline to the number of radioactive blood samples which can be safely collected and processed, following radioactive iodine therapy, within the limits of current radiation guidelines. Once validated, generalisations to other radioactive therapies may be considered.